Defining biomarkers in oral cancer according to smoking and drinking status - Rochefort, Juliette; Karagiannidis, Ioannis; Baillou, Claude; Belin, Lisa; Guillot-Delost, Maude; Macedo, Rodney; Le Moignic, Aline; Mateo, Véronique; Soussan, Patrick; Brocheriou, Isabelle; Teillaud, Jean-Luc; Dieu-Nosjean, Marie-Caroline; et al. (Frontiers in Oncology, 2023)
Purpose: Oral Squamous Cell Carcinomas (OSCC) are mostly related to tobacco consumption eventually associated to alcohol (Smoker/Drinker patients: SD), but 25-30% of the patients have no identified risk factors (Non-Smoker/Non-Drinker patients: NSND). We hypothesized that these patients have distinguishable immune profiles that could be useful for prognosis. Experimental Design: Cells present in immune tumor microenvironment (TME) and blood from 87 OSCC HPV-negative patients were analyzed using a multiparameter flow cytometry assay, in a prospective case-control study. Cytokine levels in tumor supernatants and blood were determined by a cytometric bead array (CBA) assay. Normal gingiva and blood from healthy donors (HD) were used as controls. Results: A significant increase of granulocytes (p<0.05 for blood), of monocytes-macrophages (p<0.01 for blood) and of CD4+ T cells expressing CD45RO and CCR6 (p<0.001 for blood; p<0.0001 for TME) as well as higher levels of IL-6 (p<0.01 for sera, p<0.05 for tumor supernatant) were observed in SD patients as compared to NSND OSCC patients and HD. High percentages of CD4+ T cells expressing CD45RO and CCR6 cells in tumor tissue (p=0.05) and blood (p=0.05) of SD OSCC patients were also associated with a poorer prognosis while a high percentage of regulatory T cells (Treg) in tumor tissue was associated with a more favorable prognostic factor (p=0.05). Also, a higher percentage of blood CD8+ T lymphocytes among CD45+ cells in NSND patients was associated with a better disease-free survival (p=0.004). Conclusion: Granulocytes, monocytes-macrophages, and CD4+ T cells expressing CD45RO and CCR6 in blood and TME as well as serum IL-6 can therefore distinguish OSCC SD and NSND patients. Quantifying the proportion of CD4+ T cells expressing CD45RO and CCR6 and of Treg in SD patients and CD8+ T cells in NSND patients could help defining the prognostic of OSCC patients.